Mineral supplementation for beef cattle – a meta-analysis (Research, Society and Development, 2022)
Beef cattle farming in Brazil is based predominantly on pastures. However, it is necessary to recognize the seasonal fluctuations regarding the composition and concentration of nutrients available in these pastures throughout the year in the different biomes of the Brazil. In this sense, it is also expected fluctuations in the availability of minerals through feed for cattle, which can generate deficiencies, requiring supplementation. This study aimed to deepen the knowledge on mineral supplementation of beef cattle, in different production systems, through the investigation of works already published on the subject, in the last twenty years and available in national scientific databases. It was possible to show that mineral supplementation involves several stages of planning for the production of beef cattle, and the producer must have a wide view of the system. This vision ranges from soil analysis, pasture implantation and management, the requirements of different animal categories and at different seasons of the year, to adjustments in the formulation of supplements that were available to animals because, if poorly formulated, they can cause losses irreparable in cattle. Thus, conclude that the correct use of mineral supplements will bring income through superior productivity and compensatory investments with the purchase of supplements.